1989
DOI: 10.1073/pnas.86.6.2003
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin analogues inhibit growth of pancreatic cancer by stimulating tyrosine phosphatase.

Abstract: Several analogues of somatostatin were examined in the Mia PaCa-2 human pancreatic cancer cell line for their ability to promote tyrosine phosphatase activity affecting the receptors for the epidermal growth factor. The inhibition of growth of the Mia PaCa-2 cells in culture was also evaluated to determine the mechanism of action of somatostatin analogues and their relative effectiveness in inhibiting cancer growth. Of the analogues tested D-Phe-Cys-Tyr-D-Trp-LysVal-Cys-Trp-NH2 (RC-160) caused the greatest sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
148
2
6

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(169 citation statements)
references
References 24 publications
13
148
2
6
Order By: Relevance
“…These hormones have been shown to have trophic effects on the growth of normal pancreas and also on pancreatic tumours (Johnson, 1981;Schally et al, 1986). It has therefore been proposed that somatostatin may be capable of inhibiting pancreatic tumour growth indirectly via the suppression of secretion of pancreatic trophic hormones and/or by direct effects on the tumour itself Liebow et al, 1989). Redding et al (1984) described the inhibition of both rat and hamster experimental pancreatic cancer growth by the administration of somatostatin-14.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These hormones have been shown to have trophic effects on the growth of normal pancreas and also on pancreatic tumours (Johnson, 1981;Schally et al, 1986). It has therefore been proposed that somatostatin may be capable of inhibiting pancreatic tumour growth indirectly via the suppression of secretion of pancreatic trophic hormones and/or by direct effects on the tumour itself Liebow et al, 1989). Redding et al (1984) described the inhibition of both rat and hamster experimental pancreatic cancer growth by the administration of somatostatin-14.…”
mentioning
confidence: 99%
“…Singh and colleagues (1991) have since shown that one of these xenografts expressed specific binding sites for somatostatin. It has been claimed that in vitro, somatostatin-14, and its analogue RC-160, reverse the growth-potentiating effects of epidermial growth factor (EGF) on the human pancreatic carcinoma cell line MiaPaCa-2 (Liebow et al, 1986) through the promotion of tyrosine phosphatase activity (Liebow et al, 1989). For somatostatin to impair directly the growth of pancreatic cancer the cells should therefore express receptors for the peptide.…”
mentioning
confidence: 99%
“…However, discrepancies with octreotide have been described, especially with regard to binding to a number of human cancers, like those of the breast, ovary, exocrine pancreas, prostate and colon [14][15][16][17][18]21 ]. Therefore, radioiodinated RC-160 might be an important radiopharmaceutical, having potential advantages over radioiodinated octreotide for the in vivo detection of the aforementioned somatostatin receptorpositive tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Radioiodinated [Tyr3]octreotide is frequently used for the in vitro determination of the presence of somatostatin receptors [13]. Recently, several reports have been published on the in vitro binding to somatostatin receptors of another somatostatin analogue, the octapeptide RC-160 [14][15][16]. It has been reported that RC-160 has a higher affinity than octreotide for the somatostatin receptor in human breast, ovarian, exocrine pancreatic, prostatic and colonic cancers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation